Farmer perceptions on goat kids pre-weaning mortality in KwaZulu-Natal and Eastern Cape Provinces of South Africa - Segakoeng, Moeketsi; Mtileni, Bohani; Mpofu, Takalani; Mchunu, Ayanda; Bixa, Ongeziwe; Nini, Simphiwe; Matelele, Tlou; Hadebe, Khanyisile (Frontiers in Animal Science, 2026)
Community-based breeding programs (CBBPs) are promoted as an ideal model for farmer-focused research and as an improvement strategy of indigenous goats in various developing countries. The Agricultural Research Council - Biotechnology Platform (ARC-BTP), in collaboration with the Kaonafatso ya Dikgomo (KyD) recording scheme, initiated two CBBP sites to improve animal recording and goat production in these regions. The aim of this effort was to identify community-level interventions on kid mortality, which is one of the key limitations for market competitiveness in numbers and quality of the animals produced in these communities. Individual interviews were conducted on 195 goat farmers from Anders Mission, Giff, Mxhaxho, Mantlaneni and Ncera villages in the Eastern Cape province (n = 150), and Ophande, Ezinkunini, Machibini and Majozini villages in the KwaZulu-Natal province (n = 45), covering neighboring villages in Buffalo City and uMkhanyakude Districts, respectively. The study used semi-structured questionnaires to determine the farmers’ perceptions on the causes of mortality, drawing from focus group discussions and questionnaire surveys. Majority of the participants were males (68%) aged between 30 to 82 years. Of these goat farmers, 42.1% had primary formal school, but all could read and write. Majority (56.4%) relied on old age pension as source of income, followed by livestock sales (24.1%). The average number of years in farming was 15.48 ± 14.58, and other animal species kept included chickens, cattle, sheep, pigs and dogs. The animals were extensively managed on communal land. The average goat herd sizes were 17.71 ± 11.52 in Buffalo City and 13.06 ± 11.52 in uMkhanyakude, with 22% made up of kids across the regions, respectively. Diarrhea, heartwater and starvation were the strongest (p<0.001) farmer-identified predictors of pre-weaning kid mortality with incidence rate ratios of 1.93, 1.58 and 2.52, respectively. These causes may stem from the low-input extensive production systems u. Intervention programs such as CBBPs, which integrate farmer training, resource sharing, and access to expert technical guidance, can address both primary and secondary causes of pre-weaning goat kid mortality, thereby improving productivity under the current and future production systems while conserving important South African goat genetic resources.